Gathered: A Theology for Institutions in a Changing Church - Dustin D. Benac (Religions, 2024)
Practical theology has historically engaged in sustained theological reflection on the practices of the Church that intersect with the practices of the world. As field of study, it engages in interdisciplinary engagement that combines social and theological forms of reasoning and analysis. As a broader field of praxis, it seeks to support the conditions where people of faith are formed, and communities of faith may flourish. In both expressions, practical theology exists in a dynamic relationship to institutions (e.g., congregations, denominations, universities) and contributes research and praxis that supports the future of institutions and the faith they mediate. While institutions are often the source and site of practical theology, “institutions” are taken for granted as a clearly-identifiable social form and a fixed expression. However, transnational changes in congregations and related faith-based institutions require an account of the nature and role of institutions within practical theology. In this gap, this paper advances a two-part argument: first, institutions are sites of multimodal gathering, creating containers for various forms of encounter where individuals and communities gather around a shared context, shared stories, shared practices, shared resources, and a shared journey. Second, theology for institutions can be sustained by attending to five modes of institutional engagement and analysis that are marked by attention to shared context, narratives, practices, resources, and a journey. Three sections advance this argument. The first part introduces three different situations of institutional encounter to question the relationship between theology and institutions amid a changing organizational landscape. The second part engages Alasdair MacIntyre as an interpretive framework to identify the gap of institutions in the field of practical theology. The third part concludes by detailing the structure of a theological account that resolves this gap in the field and may attend to the forms of gathering institutions provide.